Sperm cryopreservation of a live-bearing fish, the platyfish Xiphophorus couchianus - Huang, Changjiang (Theriogenology, 2004)
The objectives of this study were to evaluate the effects of cryoprotectant, osmotic pressure, cooling rate, equilibration time, and sperm-to-extender ratio, as well as somatic relationships of body length, body weight, and testis weight to sperm density in the platyfish Xiphophorus couchianus. Sperm motility and survival duration after thawing were significantly different between cryopreservation with dimethyl sulfoxide (DMSO) and glycerol, with the highest motility at 10 min after thawing obtained with 14% glycerol. With subsequent use of 14% glycerol as cryoprotectant, the highest motility after thawing was observed with Hanks’ balanced salt solution (HBSS) across a range of 240–300 mOsm/kg. Samples cooled from 5 to −80 °C at 25 °C/min yielded the highest post-thaw motility, although no significant difference was found for cooling rates across the range of 20–30 °C/min. In addition, the highest motility after thawing was found in samples equilibrated from 10 to 30 min with 14% glycerol and cooled at 25 °C/min. The post-thaw motility declined rapidly with use of 10% glycerol and cooling at 5 °C/min across the equilibration range of 10 min to 2 h. Sperm motility with a dilution ratio of sperm to extender of 1:10 was not different at 10 min after thawing with those samples at greater dilutions, but declined significantly from Day 1 after thawing and showed lower survival duration when stored at 4 °C. However, the additional dilution of sperm solutions with HBSS (300 mOsm/kg) immediately after thawing significantly slowed the decline of motility and prolonged the duration of survival. Based on the above findings, the highest average sperm motility (78 ± 3%) at 10 min after thawing was obtained when sperm were suspended in HBSS at 300 mOsm/kg with 14% glycerol as cryoprotectant, diluted at a ratio of sperm to HBSS–glycerol of 1:20, equilibrated for 10 min, cooled at 25 °C/min from 5 to −80 °C before plunging into liquid nitrogen, and thawed at 40 °C in a water bath for 7 s. If diluted within 5 h after thawing, sperm frozen by the above protocol retained continuous motility for 15 days when stored at 4 °C.